Excitonic absorption and defect-related emission in three-dimensional MoS2 pyramids. Issue 4 (17th December 2021) - Negri, M.; Francaviglia, L.; Kaplan, D.; Swaminathan, V.; Salviati, G.; Fontcuberta i Morral, A.; Fabbri, F.
Abstract : In this work, we study the excitonic absorption and cathodoluminescence emission of MoS2 micro-pyramids grown by chemical vapor deposition on SiO2 substrates, obtained at room and cryogenic temperatures. Abstract : MoS2 micro-pyramids have demonstrated interesting properties in the fields of photonics and non-linear optics. In this work, we show the excitonic absorption and cathodoluminescence (CL) emission of MoS2 micro-pyramids grown by chemical vapor deposition (CVD) on SiO2 substrates. The excitonic absorption was obtained at room and cryogenic temperatures by taking advantage of the cathodoluminescence emission of the SiO2 substrate. We detected the CL emission related to defect intra-gap states, localized at the pyramid edges and with an enhanced intensity at the pyramid basal vertices. The photoluminescence and absorption analysis provided the Stokes shift of both the A and B excitons in the MoS2 pyramids. This analysis provides new insights into the optical functionality of MoS2 pyramids. This method can be applied to other 3D structures within the 2D materials family.